Analysis of Financial System Stability in Southeast Asia (Indonesia, Singapore and Malaysia) During Covid-19 - Raudah, Raudah; Zulfa, Andria; Sakuntala, Dwita (Jurma : Jurnal Program Mahasiswa Kreatif, 2024)
This research examines the simultaneous influence of maintaining financial system stability through inflation and exchange rates. The research was conducted in three countries, Indonesia, Singapore and Malaysia, and lasted for seventeen months from 2019 to 2020. The method used was the simultaneity method. The research results show in Equation I that interest rates, consumption and exchange rates simultaneously influence inflation, but the money supply does not. Then, the results in Equation II show that Foreign Exchange Reserves and Inflation simultaneously influence the Exchange Rate, but Exports do not influence the Exchange Rate. Therefore, in controlling the financial system, the Central Bank must monitor consumption variables, interest rates and exchange rates to control inflation so that the financial system remains stable, as well as monitor foreign exchange reserves and inflation so that exchange rates in Indonesia, Singapore and Malaysia are maintained.